Cystadenocarcinoma in the lip: A report of two cases. Issue 3 (May 2023) - Watanabe, Miki; Yagisawa, Junko; Ichikawa, Hideki; Tanaka, Jun-ichi; Kato, Hiroyuki; Ito, Aki
Abstract: Cystadenocarcinoma is an extremely rare lesion with a low incidence rate of 0.18% of all salivary gland tumors in the oral and maxillofacial region. Here, we report two cases of cystadenocarcinoma in the lip. Case 1 was of a 79-year-old woman who presented with discomfort in the right upper lip. On examination, a 16 × 10 mm mass was observed on her right upper lip. The superficial mucosa was smooth but with an irregular margin. The mass was clinically suspected to be a malignant tumor, and tumor resection was performed. Case 2 was of a 51-year-old man who presented with a 20 × 20 mm mass on the left lower lip. The mass was hard, and adhesion to the skin was suspected. On T2-enhanced magnetic resonance imaging, high signal intensity and internal non-uniform features were noted. Before the operation, fine-needle aspiration cytology was performed, and atypical cells were observed; therefore, resection was performed assuming a malignant tumor. The surgeries were performed 3 years ago, and no recurrence or lymph node metastasis has been observed in either case to date.